Transpacific partnership agreement and ISP liabilities: a comparative overview between Malaysia and other member countries - Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Daud, Mahyuddin; Alavi, Rokiah (2016)
Ideally, Internet service providers’ (ISP) should not be responsible for the contents that transit through their services, as they have no editorial control over them. The U.S. Digital Millennium Copyright Act (DMCA) contains safe harbor provisions to limit ISP's liability on the ground of copyright infringement, unless they received a notice and takedown request from a copyright holder. This model has been transposed into other jurisdictions through the recently signed Trans-Pacific Partnership (TPP) Agreement between the United States of America and 11 other countries in Asia and Pacific Region. This in effect will mandate ISPs to expeditiously remove or disable access to alleged infringing material upon acquiring actual or constructive knowledge of the infringement. This TPP obligation apparently goes beyond the normal standards in the international treaties and national standards in the US as well as in Malaysia. For Malaysia, notice and takedown procedure was already in place since 2012, that i.e. few years before the signing of TPP Agreement. Set on this background, the objective of this paper is to analyze and draw some significant comparisons between TPP obligations in Malaysia with other eleven (11) TPP member countries in relation to ISP's liabilities. The discussion embraces notice and takedown requirements and other related matters such as ‘safe harbour’ provisions and incentives which are made available to ISPs. The paper concludes with the forthcoming effect of TPP on relevant Malaysian legislations and the inherent need of striking a balance between the different interests at stake namely the ISP, the copyright owner and the public net-users at large.